1998
DOI: 10.4315/0362-028x-61.6.735
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Chemical Changes in High-Pressure-Treated Milk during Refrigerated Storage

Abstract: The microbiological and biochemical changes during storage of high-pressure-treated (400 MPa at 25 degrees C, for 30 min) whole (3.5% fat) and skim (0.3% fat) milk at refrigeration temperatures (7 degrees C) were studied. From a microbiological point of view, high-pressure treatment of milk led to an increase in the shelf life because, after 45 days of refrigerated storage, the psychotrophic and pseudomonad counts of the pressurized milk were lower than those of the unpressurized milk after 15 days. Capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 0 publications
3
23
1
1
Order By: Relevance
“…The low level of proteolysis is probably due to the low activity of plasmin at refrigeration temperatures. Garcia-Risco et al [7] observed little difference between the level of proteolysis in untreated milk and milk treated at 400 MPa for 30 min, during storage at 7°C for 15 d; however, in the present study (Tab. II) milk treated under such conditions had slightly faster proteolysis than untreated milk on storage at 5 °C.…”
Section: Discussioncontrasting
confidence: 82%
“…The low level of proteolysis is probably due to the low activity of plasmin at refrigeration temperatures. Garcia-Risco et al [7] observed little difference between the level of proteolysis in untreated milk and milk treated at 400 MPa for 30 min, during storage at 7°C for 15 d; however, in the present study (Tab. II) milk treated under such conditions had slightly faster proteolysis than untreated milk on storage at 5 °C.…”
Section: Discussioncontrasting
confidence: 82%
“…In milk, plasmin activity was reported to resist at least 400 MPa for 30 min at 25 1C (Garcı´a-Risco, Corte´s, Carrascosa, & Lo´pez-Fandin˜o, 1998). Huppertz et al (2004g) found that treatments at 400 and 600 MPa at 20 1C for 30 min reduced plasmin activity by 30% and 75%, respectively.…”
Section: Effects Of High Pressure On Native Milk Enzymesmentioning
confidence: 96%
“…Quantification of the levels of denatured b-Lg present in the casein fraction showed that pressure-induced b-Lg denaturation was not reversible during two months at 77C [46]. The same CZE method was used to follow the distribution of proteins, after the separation of the micellar and serum phases of pressurized milks by ultracentrifugation, which was related with mineral changes and technological properties of pressurized milks [47].…”
Section: Assessment Of Technological Processesmentioning
confidence: 99%